OC-104 Long term effectiveness of short chain fermentable carbohydrate (FODMAP) restriction in patients with irritable bowel syndrome. (22nd June 2015) - Martin, L; van Vuuren, C; Seamark, L; Williams, M; Staudacher, H; Irving, PM; Whelan, K; Lomer, MC
Abstract : Introduction: Short chain fermentable carbohydrate (FODMAP) restriction reduces symptoms of irritable bowel syndrome (IBS) and is routinely used in clinical practice. Comprehensive FODMAP education is provided by registered dietitians and incorporates a low FODMAP exclusion phase for 4–8 weeks followed by FODMAP reintroduction to individual tolerance. Patients are empowered to self-manage their diet and symptoms, however whether this approach is effective in the long term is unknown. This study aimed to assess the long term effectiveness of the low FODMAP diet in patients with IBS. Method: Patients with IBS (n = 358) from primary and secondary care were invited to take part in a prospective questionnaire study after completion of comprehensive FODMAP education as described above. Symptoms were assessed at baseline before FODMAP education, following FODMAP exclusion (4–8 weeks) and following FODMAP reintroduction (6–18 months) using the global symptom question "Do you currently have satisfactory relief of your gut symptoms?" and the Gastrointestinal Symptom Rating Scale. Dietary adherence to long term FODMAP restriction was assessed using a Likert scale. Statistical analyses used the chi-squared test. Results: One hundred patients consented and returned questionnaires (age: mean ± sd; 49 ± 15 years, female: n = 74). At baseline, 10 patients reported satisfactory relief of symptoms. Following FODMAP exclusion, 62 patients reported satisfactory relief. Of these, 44/62 (71%) continued to report satisfactory relief at one year following FODMAP reintroduction, with 42 patients continuing to avoid high FODMAP foods at least 50% of the time. Of the patients who reported satisfactory relief following FODMAP exclusion (n = 62) compared to those who did not (n = 38), significantly more patients at one year reported absent or mild abdominal pain (n = 51 vs n = 19; P = 0.001), bloating (n = 46 vs n = 17; P = 0.003), flatulence (n = 43 vs n = 11; P < 0.001), borborygmi (n = 47 vs n = 19; P = 0.008), urgency (n = 46 vs n = 17; P = 0.003), sensation of incomplete evacuation (n = 46 vs n = 19; P = 0.014) and lethargy (n = 44 vs n = 19; P = 0.035). Conclusion: The majority of patients who achieve satisfactory relief of symptoms following FODMAP exclusion continue to have satisfactory relief at one year indicating that FODMAP education is useful for long term symptom control and self-management. The majority of patients continue to avoid high FODMAP foods in their diet at least half the time. Disclosure of interest: None Declared.